Circulating Immune Complex in Glomerular Diseases - H. Alatas; I. G. N. Wila Wirya; Taralan Tambunan; S. Cornain; Sucahyo Sucahyo; S. Himawan; Gunardjono Gunardjono (Paediatrica Indonesiana, 1982)
Circulating Immune Complex (CIC) in the serum have been studied in 75patients with glomerular diseases. The highest positive rate in patients with post streptococcal glomerulonephritis and lupus nephritis were respectively 83.3% atld 75%.In nephrotic syndrome: 33.3% (5 jl5) was positive in diffuse mesangial proliferative cases, and in all 3 patient~Â· with membranoproliferative glomerulonephritis, membranous nephropathy and focalÂ  glomerulosclerosis. All of them had detectable immune deposits in the glomeruli.In minimal lesion nephrotic syndrome (MLNS) without glomerular immunedeposits, CIC was positive in 2 out of 17 cases (12%). This support the hypothesis that in MLNS a humoral immune mechanil'im might take part in the pathogenesis of the disease.